Anomalous Channel‐Length Dependence in Nanofluidic Osmotic Energy Conversion. (13th January 2017) - Cao, Liuxuan; Xiao, Feilong; Feng, Yaping; Zhu, Weiwei; Geng, Wenxiao; Yang, Jinlei; Zhang, Xiaopeng; Li, Ning; Guo, Wei; Jiang, Lei
Abstract : Recent advances in materials science and nanotechnology have lead to considerable interest in constructing ion‐channel‐mimetic nanofluidic systems for energy conversion and storage. The conventional viewpoint suggests that to gain high electrical energy, the longitudinal dimension of the nanochannels ( L ) should be reduced so as to bring down the resistance for ion transport and provide high ionic flux. Here, counterintuitive channel‐length dependence is described in nanofluidic osmotic power generation. For short nanochannels (with length L < 400 nm), the converted electric power persistently decreases with the decreasing channel length, showing an anomalous, non‐Ohmic response. The combined thermodynamic analysis and numerical simulation prove that the excessively short channel length impairs the charge selectivity of the nanofluidic channels and induces strong ion concentration polarization. These two factors eventually undermine the osmotic power generation and its energy conversion efficiency. Therefore, the optimal channel length should be between 400 and 1000 nm in order to maximize the electric power, while balancing the efficiency. These findings reveal the importance of a long‐overlooked element, the channel length, in nanofluidic energy conversion and provide guidance to the design of high‐performance nanofluidic energy devices. Abstract : Anomalous channel‐length dependence is discovered in nanofluidic osmotic power generation. In contrast to conventional long nanofluidic devices, if the channel length is further reduced to below 400 nm, the output power decreases with decreasing channel length, showing anomalous, non‐Ohmic response. These findings reveal the importance of the long‐overlooked element, the channel length, in nanofluidic energy conversion.